From Meccan persecution to modern islamophobia: a historical and sociopolitical study - Nadir, Muhammad; Ahmad, Khaliq (Nun Gemilang Enterprise, 2025)
This study explores the historical foundations and contemporary realities of Islamophobia by examining the persecution of early Muslims in Mecca and comparing it with modern anti-Muslim sentiment. Through a sociopolitical and historical lens, it investigates the Quraysh’s opposition to Islam, rooted in tribal authority, economic control, and religious monopoly. The paper analyses key events, such as the Prophet Muhammad’s (SAW) peaceful resistance, migration to Medina, and the formation of the Charter of Medina, as transformative strategies of community-building and interfaith coexistence. Drawing parallels between classical and modern Islamophobia, the study applies conceptual frameworks such as Orientalism and social identity theory to reveal structural continuities across eras. While modern Islamophobia operates through political rhetoric and media narratives, its core reflects the same fear-driven resistance to religious reform and social equality witnessed in 7th-century Arabia. The research concludes by highlighting the enduring relevance of Prophetic approaches diplomacy, inclusion, and justice as viable responses to contemporary challenges faced by Muslim minorities